PENGARUH EFISIENSI PELAYANAN DAN DIGITALISASI SISTEM ADMINISTRASI TERHADAP KUALITAS PELAYANAN AKADEMIK - Wardani Wardani; Hana Netti Purasani (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the influence of service efficiency and the digitization of administrative systems on the quality of academic services at SMK PGRI 1 Semarang. This study employs a quantitative approach using an associative method. The study population consists of all 142 tenth-grade students, with a sample of 105 respondents selected through random sampling. Data analysis used multiple linear regression with t-tests, F-tests, and the coefficient of determination (R²) test, processed using SPSS version 27. The results indicate that service efficiency has a positive and significant effect on the quality of academic services (t = 9.228; sig. = 0.000; b = 0.771); the digitization of the administrative system has a positive and significant effect on the quality of academic services (t = 4.490; sig. = 0.000; b = 0.430); and simultaneously, both variables have a significant effect on the quality of academic services (F = 91.879; sig. = 0.000) with a contribution of 64.3% (R² = 0.643). The research implications emphasize the importance of synergy between the standardization of service procedures and the continuous optimization of digital-based administrative systems.